Analisis Pengaruh Kualitas Produk, Kualitas Layanan, Harga, Dan Lokasi Terhadap Kepuasan Konsumen Di Rumah Makan Spesial Sambal Surakarta. - Tatas, Muhammad Adinandra, Drs. Wiyadi, M.M., Ph.D (2015)
The aim in this study was to analyze the influence of the Product Quality Customer Satisfaction in Special Sambal of Surakarta. Analyze the influence of Service Quality on Customer Satisfaction in Special Sambal of Surakarta. Analyze the influence of price on consumer satisfaction in Special Sambal of Surakarta. Analyze the effect of location on Customer Satisfaction in Special Sambal of Surakarta. The population in this study are all consumers who buy food in Special Sambal of Surakarta while used as a sample of 100 respondents. The sampling technique used was purposive sampling. The analysis tool used is normality test, multicollinearity, heteroscedasticity test, test the coefficient of determination (R2), F test (Test Accuracy Model) and t test (Test of Hypothesis).Based on the results of data analysis known variable product quality and significant positive effect on customer satisfaction, meaning that the higher the consumer's perception of the quality of the product, the more powerful push consumers feel satisfied. The variable quality of service and significant positive effect on customer satisfaction,meaning that the higher consumer perceptions of quality of service, the more powerful push consumers feel satisfied. Variable price affects customer satisfaction, meaning that the higher consumers' assessment of the price, it will further strengthen customer satisfaction. Variable location affects customer satisfaction, meaning that the higher consumer ratings of the location, it will further strengthen customer satisfaction. Rated Rsquare (R2) obtained at 0,523. This means that the variation of the variable changes in consumer satisfaction can be explained by the variable quality of the product (X1), quality of service (X2), price (X3) and location (X4) amounted to 52.3%. While the remaining 47.7% is explained by other variables outside the model. Keywords: Quality Products, Quality Service, Price, Location and consumer satisfaction.